IQ TEST PROGRAM APPLICATION FOR SENIOR HIGH SCHOOL LEVEL USING MICROSOFT VISUAL BASIC 6.0 - Deni Kurniawan; Sahni Damerianta,SKom, MMSI (Jurnal Sistem Informasi, 2003)
Scientific writing contains a description of the IQ test programs, which are measuring the level of intelligence, psychological aspects, and the direction of interest in accordance with the ability of a student who was still in high school and sat dibangku second class who later IQ tests would also determine the direction will get students at third grade, using Microsoft Visual Basic 6.0.As for the first time that must be filled in this application is the biodata of students, such as: Number of Parent Participants (NIP), name, religion, Place of Birth (TTL), Gender, Class. In this IQ test programs Nip is a key which in turn will lead to problems that contain images or text that must be answered of course.Calculation results of IQ test scores obtained from the amount obtained by application users an IQ test. Then the score or the value can be classified into groups, such as: assessment of psychological aspects, and Value IQ. Then, from these assessments regrouped to assessing the direction of interest and standard of intelligence. Then end of the assessment process is concluded for the provision of an advice.